2015
DOI: 10.1371/journal.pone.0142783
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Ultrastructural Studies on the Conjunctiva of the Barred Owl (Strix varia)

Abstract: This report is the first characterization of the histology and ultrastructure of the barred owl conjunctiva. The inferior eyelid was dominated by a large disk-shaped plate covered by a non-keratinized stratified squamous or cuboidal epithelium of variable thickness. The apical surface of the plate epithelium varied from flat to long microvilli or even short cytoplasmic extensions similar to those seen in the third eyelid. All specimens had a few goblet cells filled with mucous secretory granules in the plate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…() in the adult African black ostrich and the Bilgorajska goose, the stroma of the upper and lower eyelids was composed of a dense connective tissue with densely packed collagen fibres and fibrocytes. In all of the examined birds, there were more or less numerous clusters of melanocytes, which were present, either only in the marginal zone or in all of the eyelid areas, as in the Barred owl (Jochems & Phillips, ). According to Klećkowska‐Nawrot, Goździewska‐Harłajczuk, et al.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…() in the adult African black ostrich and the Bilgorajska goose, the stroma of the upper and lower eyelids was composed of a dense connective tissue with densely packed collagen fibres and fibrocytes. In all of the examined birds, there were more or less numerous clusters of melanocytes, which were present, either only in the marginal zone or in all of the eyelid areas, as in the Barred owl (Jochems & Phillips, ). According to Klećkowska‐Nawrot, Goździewska‐Harłajczuk, et al.…”
Section: Discussionmentioning
confidence: 89%
“…There are few studies focusing on the eyelid morphology and CALT development in wild and ornamental birds, which inhabit homes, zoos and wildlife shelters. The eyelid anatomy has been described in the English sparrow, pigeon, common buzzard, hooded merganser, rockhopper penguin, common mallard, falcon, hawk, vulture, chicken, turkey, barred owl, Bilgorajska goose and African black ostrich (Bacha & Bacha, ; Bielek, ; Gultiken et al., ; Jochems & Phillips, ; Klećkowska‐Nawrot, Goździewska‐Harłajczuk, et al., ; Klećkowska‐Nawrot, Nowaczyk, et al., ; Kolmer, ; Kühnel & Schramm, ; NAA, ; Sivak & Glover, ; Wood, ). Our study revealed large variation in the anatomy of the upper and lower eyelid in the studied bird supraorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations